BUDAYA SIRI’ DAN PESSE’ DALAM BINGKAI AKUNTANSI MAKASSAR - Andi Faisal (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
This paper aims to uncover the veil of cultural capitalism in the discourse and practice of accounting today, and offers a paradigmatic change by entering values siri’ and pesse’ culture Bugis - Makassar into the discourse and practice of accounting. Cultural values of capitalism are firmly entrenched in the current accounting practice caused the practice - the practice of cheating. Cheating is suspected to occur because of the paradigm that puts the human being as subject selfish. siri and pesse’ value are integrated into the discourse and practice of accounting can make accounting have independence, honesty and integrity are more firmly entrenched in him.